Evaluating The Scheduling of The Development Projects of Rural Electricity Network Distribution Using Critical Path Method - Diqbal Satyanegara; Widya Nur Bhakti Pertiwi (Jurnal REKOMEN (Riset Ekonomi Manajemen), 2022)
Delay in the completion of a project is a problem that is often faced, it certainly has an impact on the entire project. CPM is one of the control tools to get a working picture of the project. In 2015, PT PLN South Banten Area made a Development Project of Rural Electricity Network Distribution in Banten. This project is held by an electrical installation services company, PT. Z, in June 2015.This project is due 150 days, PT. Z had defined time completion on 143 days, but the completion took 154 days. The type of research used in this research is quantitative research with analytical technique CPM approach. This research identified the least project schedule planning. There are three activities in this project schedule which are unlisted yet, therefore it affected the timeline of the project. Based on the CPM calculation, PT. Z could have shorten the work time down to 3 days with the cost of Rp 1.802.386.000